The Dissolution of Community Organizations in Indonesia: Is Court Involvement Necessary? - Ichsan , Muchammad; Prasetyoningsih, Nanik (Jurnal Penegakan Hukum dan Keadilan, 2026)
The dissolution of community organizations in Indonesia under Law No. 16 of 2017 remains controversial, particularly regarding the absence of judicial involvement. This study employs a normative juridical approach to examine the issue from three perspectives—human rights, Islamic law, and Indonesian positive law. The research relies on statutory, conceptual, and comparative analyses using primary and secondary legal materials, including the 1945 Constitution, Law No. 16 of 2017, and relevant Constitutional Court decisions. Findings reveal that although the law is constitutionally valid, it does not fully satisfy the principles of justice and due process, as it allows the government to dissolve organizations unilaterally without judicial review. From the perspective of siyasah syar’iyyah (legitimate policy), such authority must be grounded in maslahah (public interest) and fairness to prevent social discontent. Therefore, to uphold constitutional democracy and protect fundamental rights, court involvement should be reinstated as an essential mechanism in the dissolution of community organizations.